2018
DOI: 10.1111/jfd.12928
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of saprolegniosis in rainbow trout (Oncorhynchus mykiss Walbaum) using two bacterial isolates (LE89 and LE141) of Pseudomonas fluorescens

Abstract: The probiotic activity of 15 bacterial isolates that inhibit Saprolegnia parasitica in vitro was tested for the biocontrol of saprolegniosis in rainbow trout (Oncorhynchus mykiss Walbaum), adding the bacteria to tank water for 14 days at a concentration of 106 bacteria ml−1 water. Pseudomonas fluorescens LE89 and Pseudomonas fluorescens LE141 were effective in controlling experimental infection with S. parasitica since of the fish treated with LE89, 24.5% ± 16.27% (p < 0.05) became infected, as did 42.8% ± 8.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…In a previous work of our research group [11] the addition of two isolates of Pseudomonas fluorescens, LE89 and LE141, to the water in tanks for 14 days at a concentration of 10 6 bacteria/mL was able to reduce experimental infection with Saprolegnia parasitica in rainbow trout. In fact, fish treated with LE89 had a 24.5% infection rate, and those treated with LE141 a rate of 42.8%, while controls showed 100% of infection.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In a previous work of our research group [11] the addition of two isolates of Pseudomonas fluorescens, LE89 and LE141, to the water in tanks for 14 days at a concentration of 10 6 bacteria/mL was able to reduce experimental infection with Saprolegnia parasitica in rainbow trout. In fact, fish treated with LE89 had a 24.5% infection rate, and those treated with LE141 a rate of 42.8%, while controls showed 100% of infection.…”
Section: Discussionmentioning
confidence: 80%
“…The mechanisms by which probiotics stimulate the immune system are not yet well understood, but it is known that factors such as type of strain, dose, duration, and mode of administration or environmental conditions can affect the immunomodulating potency of probiotics [25]. In this work, a dose of 10 6 bacteria/mL in the water tank during two weeks was used, which may not have been sufficient to stimulate the immune system, but has been found to be effective in vivo to reduce experimental infection with S. parasitica [11].It has been suggested that immune cells in hosts do not react against the bacteria that are naturally found on their surfaces as strongly as they do against bacteria normally not present in their surroundings [29]. This might explain the very limited stimulation of the immune response by LE89 and LE141, as they were isolated from the skin surface of brown trout (Salmo trutta) and rainbow trout (Oncorhynchus mykiss) respectively [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, other treatments are used or considered for controlling Saprolegnia spp. include formalin, benzoic acid, acetic acid, iodoacetic acid and copper sulphate, along with possible biocontrol with the use of probiotics administered in water and feed (Barnes et al, 2002; González‐Palacios et al, 2018; Tedesco et al, 2018).…”
Section: Introductionmentioning
confidence: 99%